A REVIEW ON INTERSTITIAL LUNG DISEASE ASSOCIATED WITH RHEUMATOID ARTHRITIS (World Journal of Current Medical and Pharmaceutical Research, 2019)
Interstitial lung disease is a condition that causes gradual scarring of the lung tissue. This may be due to some chemical exposure or even due to substances like coal and asbestos dust. It may also tesult from auto immune conditions such as rheumatoid arthritis. The scarring which occurs in this condition is usually irreversible. The common symptoms of this condition includes dry cough and SOB on exertion. The diagnostic procedures include HRCT chest imaging, blood tests, bronchoscopy, bronchoalveolar lavage , pulmonary function tests and rarely surgical biopsy. The basic first line therapy includes corticosteroids, DMARDs based on the condition and type of ILD in the individual patient followed by a lung transplant if needed.